PENGARUH NET PROFIT MARGIN DAN DEBT TO EQUITY RATIO TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PADA PERIODE 2019-2022 - Siti Sarah; Yenny Ernitawati; M. Badrun Zaman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Good profit growth is a reflection of a healthy company, and shows good performance. This research is intended to analyze the company's financial performance Net Profit Margin (NPM) and Debt To Equity Ratio (DER) on profit growth. This research applies a quantitative approach with comparative methods. The population used was 43 companies registered on the IDX from the food sector for the 2019-2022 period. A sample of data from 26 companies for 4 years was obtained using a purposive sampling technique. Data analysis techniques use descriptive statistics, normality tests, and difference tests with the help of SPSS software. The test results show that financial performance with Net Profit Margin (NPM) and debt to equity ratio (DER) have a positive influence on profit growth.